2010
DOI: 10.1037/a0017782
|View full text |Cite
|
Sign up to set email alerts
|

Addressing religious and spiritual issues in trauma-focused cognitive behavior therapy for children and adolescents.

Abstract: Psychologists have become increasingly concerned with the role of religion and spirituality in resolving childhood physical and sexual abuse, particularly religion-related abuse. In treating victims of child abuse, trauma-focused cognitive behavior therapy has emerged as a leading treatment for recovery. In this article, we discuss the relevance of religious and spiritual issues in trauma-focused cognitive behavior therapy for children and teens. Using three case studies, we then present a model for assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 26 publications
6
65
0
3
Order By: Relevance
“…Across models, one aspect of spirituality, existential well‐being, was the only construct to significantly predict resilience for both populations. This supports previous research, which found that spirituality is an integral part of the healing and coping process, and additionally identifies that existential well‐being, an aspect of spirituality, has significant influence on greater psychological well‐being (Peres et al, ; Wachholtz & Sambamoorthi, ; Walker et al, ). Hope for the future and a lack of negative religious coping were also found to be significant predictors in those who did not have a history of abuse, which also supported previous research (Bogar & Hulse‐Killacky, ; Kagan, ; Wachholtz & Sambamoorthi, ; Walker et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Across models, one aspect of spirituality, existential well‐being, was the only construct to significantly predict resilience for both populations. This supports previous research, which found that spirituality is an integral part of the healing and coping process, and additionally identifies that existential well‐being, an aspect of spirituality, has significant influence on greater psychological well‐being (Peres et al, ; Wachholtz & Sambamoorthi, ; Walker et al, ). Hope for the future and a lack of negative religious coping were also found to be significant predictors in those who did not have a history of abuse, which also supported previous research (Bogar & Hulse‐Killacky, ; Kagan, ; Wachholtz & Sambamoorthi, ; Walker et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Spirituality is distinct from religion, because religion is described as a structured framework of a particular set of beliefs (Robert & Kelly, 2015). Researchers have found that many individuals already turn to spirituality as a form of coping during a traumatic event (Peres et al, 2007;Walker et al, 2010). Wachholtz andSambamoorthi (2011) andWalker et al (2010) found that spirituality positively affected individuals' perceived and objectively measured physical health and psychological well-being after a trauma.…”
Section: Spirituality and Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study comparing effectiveness of cognitive therapy that used religious imagery, even when the therapist was nonreligious, the cognitive therapy with religious elements was slightly more effective at follow-up among religious adults (Propst, Ostrom, Watkins, Dean, & Mashburn, 1992). Fuller discussions of therapeutic work that allow religious and spiritual assessment and inclusion of religious frameworks and potential pitfalls are available (Canda, 2010;Hodge, 2011;Lukoff, Lu, & Turner, 1998;Walker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although not generally studied in conjunction with child and adolescent interventions, R/S coping strategies have proven effective in helping individuals make sense of loss and trauma as well as helping individuals improve their life satisfaction (Ano & Vasconcelles, 2005; Aten et al, 2014; Bryant‐Davis et al, 2012; Walker & Hathaway, 2013). In the professional literature specific to children's counseling needs, R/S needs have been considered when assisting children with a history of sexual abuse (Walker, Reese, Hughes, & Troskie, 2010); encouraging victims to offer forgiveness to those who have inflicted harm (Diblasio, Worthington, & Jennings, 2013); and supporting healing in children exposed to traumatic events (Bryant‐Davis et al, 2012).…”
Section: Supportive Religious and Spiritual Strategiesmentioning
confidence: 99%